R(x)=x(23-.07x)

Simple and best practice solution for R(x)=x(23-.07x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for R(x)=x(23-.07x) equation:


Simplifying
R(x) = x(23 + -0.07x)

Multiply R * x
xR = x(23 + -0.07x)
xR = (23 * x + -0.07x * x)
xR = (23x + -0.07x2)

Solving
xR = 23x + -0.07x2

Solving for variable 'x'.

Reorder the terms:
-23x + xR + 0.07x2 = 23x + -0.07x2 + -23x + 0.07x2

Reorder the terms:
-23x + xR + 0.07x2 = 23x + -23x + -0.07x2 + 0.07x2

Combine like terms: 23x + -23x = 0
-23x + xR + 0.07x2 = 0 + -0.07x2 + 0.07x2
-23x + xR + 0.07x2 = -0.07x2 + 0.07x2

Combine like terms: -0.07x2 + 0.07x2 = 0.00
-23x + xR + 0.07x2 = 0.00

Factor out the Greatest Common Factor (GCF), 'x'.
x(-23 + R + 0.07x) = 0.00

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-23 + R + 0.07x)' equal to zero and attempt to solve: Simplifying -23 + R + 0.07x = 0 Solving -23 + R + 0.07x = 0 Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + R + 23 + 0.07x = 0 + 23 Reorder the terms: -23 + 23 + R + 0.07x = 0 + 23 Combine like terms: -23 + 23 = 0 0 + R + 0.07x = 0 + 23 R + 0.07x = 0 + 23 Combine like terms: 0 + 23 = 23 R + 0.07x = 23 Add '-1R' to each side of the equation. R + -1R + 0.07x = 23 + -1R Combine like terms: R + -1R = 0 0 + 0.07x = 23 + -1R 0.07x = 23 + -1R Divide each side by '0.07'. x = 328.5714286 + -14.28571429R Simplifying x = 328.5714286 + -14.28571429R

Solution

x = {0, 328.5714286 + -14.28571429R}

See similar equations:

| 14.5s+19.93=10.3s-19.91-16.02 | | x+8.5=14.2 | | -12h=-11h-12 | | 3/4(x-5)+x=x | | 4m+15=6m-17 | | -11+9u=18u-1-14u | | -4+7q=8q-7-3 | | 0.5k+1.5=3 | | -4-t=-4+t | | 3x+7=7x+15 | | 15/6=n/12 | | 0.6x+2=0.7+2 | | -10-7w-10=7-4w | | 4-3cot=1 | | 40=8(x-8) | | X^2-12X-4.5=0 | | P=2x+3 | | -8y=-6-9y | | -3(5+2x)=-2x+13 | | 8-(4x-12)=8x-(3x-2) | | 2-5f=-7f+10 | | 4+2y=10-4y | | 3/5=6n | | -j=j-8 | | -5x(4x-8y^2+4)= | | 10-6n=-6-10n | | 3b-11=3+b | | 7x-14=7(x+4) | | 5+10d=9d | | 6x-(10-2x)=3x+5 | | 9b+3=22 | | 18.9125-(1/4)= |

Equations solver categories